Desain Pembelajaran Pendidikan Agama Islam (PAI) dengan Pendekatan Deep Learning di SMA - Abdussyukur; Zulfah, Hefty (Malewa: Journal of Multidisciplinary Educational Research, 2025)
This study aims to formulate a conceptual design for Islamic Religious Education (PAI) learning in senior high schools based on the Deep Learning (DL) approach. The research employs a qualitative approach, utilising library research and conceptual analysis methods. The primary source of this study is the academic manuscript "Deep Learning Towards Quality Education for All," published by the Ministry of Education, Culture, Research, and Technology, along with other relevant scholarly literature. Data were analysed by identifying, examining, and synthesising key concepts, which were then contextualised within the design of PAI learning at the senior high school level. The findings indicate that the design of PAI learning based on the DL approach can be structured around four main frameworks: (1) the eight dimensions of the Pancasila Student Profile; (2) the principles of meaningful, mindful, and joyful learning; (3) stages of learning experiences, including understanding, applying, and reflecting; and (4) the learning environment, which encompasses pedagogical practices, collaboration, digital technology, and cultural ecosystems.